Genetics, molecular control and clinical relevance of habituation learning - Blok, Laura Elisabeth Rosalie; Boon, Marina; van Reijmersdal, Boyd; Höffler, Kira Daniela; Fenckova, Michaela; Schenck, Annette (Neuroscience and biobehavioral reviews, 2022)
Habituation is the most fundamental form of learning. As a firewall that protects our brain from sensory overload, it is indispensable for cognitive processes. Studies in humans and animal models provide increasing evidence that habituation is affected in autism and related monogenic neurodevelopmental disorders (NDDs). An integrated application of habituation assessment in NDDs and their animal models has unexploited potential for neuroscience and medical care. With the aim to gain mechanistic insights, we systematically retrieved genes that have been demonstrated in the literature to underlie habituation. We identified 258 evolutionarily conserved genes across species, describe the biological processes they converge on, and highlight regulatory pathways and drugs that may alleviate habituation deficits. We also summarize current habituation paradigms and extract the most decisive arguments that support the crucial role of habituation for cognition in health and disease. We conclude that habituation is a conserved, quantitative, cognition- and disease-relevant process that can connect preclinical and clinical work, and hence is a powerful tool to advance research, diagnostics, and treatment of NDDs.
Keywords: učení; neurovývojové poruchy; Habituation; Gene list; Molecular pathway; Autistic Disorder; Neurodevelopmental Disorders; Learning; Animals; lidé; Humans; zvířata; habituace (psychofyziologie); Neurodevelopmental disorders; autistická porucha; Habituation, Psychophysiologic; Molecular Biology; molekulární biologie; Cognition